Co-creating Wellby—a mobile app and wearable for student well-being management guided by a needs assessment and co-design - Laiti, Justin; Donnelly, Jennifer; Byrne, Elaine; Dunne, Pádraic J. (Frontiers in Digital Health, 2025)
BackgroundAdolescents need additional well-being support, particularly in stressful periods such as during the final years of secondary school. These students are growing up in an increasingly digital world, however there is a lack of mobile applications specifically designed to support adolescent students' well-being. Because of this, there is a need for co-created digital tools that are built to promote thriving in this population. The aim of this study was to explore how digital tools, such as a mobile app and wearable, can be used to address Irish secondary school student well-being needs through a collaborative co-design process with students.MethodsGroups of students at four schools were sent a needs assessment to understand student's most pressing well-being needs. Co-design sessions were conducted with a group of students at each school, following the confirmation of stress and sleep as students' main well-being priorities and their interest in digital support tools.ResultsStudents' conversations and designs from these sessions helped to uncover important elements of a well-being toolkit that they named, Wellby. The Wellby toolkit is comprised of a bespoke mobile app and wearable device for use by individuals. Participating students identified requisite elements of Wellby support that included self-tracking tools, supports for stress, and customizable features.DiscussionThese insights from Irish secondary school students helped to shape a student-centered well-being support tool and provide an example of co-created positive technology.